Epizootic peculiarities of dog ctenocephalosis in the conditions of the town of Poltava - Нorb K.O. (Scientific Progress & Innovations, 2019)
The aim of the article is to study the epizootic peculiarities of dog ctenocephalosis on the territory of the town of Poltava, as ctenocephalosis is one of the most widely spread dog diseases, caused by fleas of genus Ctenocephalides. Methods of the research. The following scientific methods were the methodological basis of the research: analysis and synthesis (establishing infestation indices of dogs by fleas; determining age dynamics of dog ctenocephalosis); theoretical search and abstract-logical (the analysis of the research as to the disease incidence of dog ctenocephalosis, caused by fleas of genus Ctenocephalides); graphical (the reflection of the research results by graphics). The research results. The research results as to studying the spreading of dog ctenocephalosis on the territory of Poltava were given in the article. The indices of the invasion prevalence depending on animals’ breed and age were taken into account. Entomological examination was conducted by combing out animals’ hair-coat covering and collecting fleas from their typical places of inhabiting on the dogs’ body. Ctenocephalosis was revealed by us in dogs older than one year. However, dogs are maximally infested by fleas at the age from one to six years (EI - 50,0–62,8 %). It was found out, that dogs of hunting breeds (ЕІ – 53,5 %) and non-pedigree animals (ЕІ – 60,7 %) are susceptible to ctenocephalosis causal agents most of all. The dogs of ornamental breeds were the least infested (ЕІ – 18,6 %). The elements of scientific novelty. It has been established, that ctenocephalosis is a widely spread invasion on the territory of Poltava. Moreover, the animals of both sexes turned out to be susceptible to flea infestation. Infestation indices of dogs with fleas were determined; age dynamics of dog ctenocephalosis was defined; breed susceptibility of dogs to ctenocephalosis causal agents was investigated. Practical importance. The studying of epizootic situation as to dog ctenocephalosis in Poltava was conducted according to the research results of animals from different administrative districts of Poltava; the dogs were examined in the veterinary service “Vetexpert” during 2017-2018. In all, 187 dogs were examined. The average prevalence of infestation was 43,85%. It was established, that the most susceptible to blood-sucking insects among the dogs of ornamental breeds are the Chinese chihuahua (50%), hunting breeds –Labrador-retriever and cocker spaniel (60,0% - 63,6%), utility breeds – German sheep-dog and American Staffordshire terrier (62,9 – 71,4%).